Differences in biological maturity status and predicted adult height between selected and non-selected players: an investigation of male and female athletes in youth elite basketball - Leyhr, D.; Roesch, D.; Villmeter, F.; Höner, O. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION The influence of biological maturity on talent identification in physically demanding sports is critically debated within both, research and practice. Especially during adolescence, maturity-related performance differences within the same age group may cause greater chances of being selected and promoted for early-maturing athletes (Malina et al., 2019). Though increasing interest is dedicated to maturity-related parameters in talent identification and development in general, evidence of its impact for talent identification in Basketball is still scarce. However, particularly in Basketball, maturity-related indicators (e.g., body height) are considered relevant for performance. Accordingly, the aim of the present study was to analyze differences in the biological maturity status and predicted adult height between selected and non-selected male and female youth basketball players for the German U15 and U16 youth national teams.